Green Innovation and Firm Performance in Jakarta’s Bakery MSMEs: The Influence of Absorptive Capacity, GSCM, Organizational Learning, and Market Turbulence - Karnadji, Djati; Arafah, Willy; Wahyudi, Agustinus Sri (Universitas Mercu Buana, 2023)
This study aims to explore the influence of absorptive capacity, green supply chain management, organizational learning, and market turbulence on green innovation and firm performance in the MSME bakery industry in Indonesia. The research design is quantitative research using exploratory research. Data were collected from 210 respondents of bakery MSME business actors specializing in sweet or fresh bread located in Jakarta and surrounding areas. Data analysis using PLS-SEM. The analysis consists of descriptive statistics, measurement model evaluation, structural model evaluation, and hypothesis testing. The results showed that absorptive capacity, organizational learning, and green innovation affect firm performance, while green supply chain management and market turbulence have no effect on firm performance. Absorptive capacity affects green innovation, but green supply chain management and organizational learning have no effect on green innovation. Other findings show that market turbulence does not moderate the relationship between green innovation and firm performance, so green innovation does not mediate the relationship between absorptive capacity, green supply chain management, and organizational learning and firm performance. In this study, absorptive capacity is the most influential exogenous variable on the endogenous variables of green innovation and firm performance. These results contribute to the strategic management literature and the resource-based view (RBV), dynamic capability, knowledge-based view (KBV), agency theory, and legitimacy theory theories used in this study.